(untitled) (Revista de Ciências Agroveterinárias, 2025)
In southern Brazil, the high annual rainfall and soil pH conditions increase the potential for boron (B) leaching. This study aimed to examine B dynamics in soil and the responses of soybean (Glycine max (L.) Merr.) crops to surface application of B sources with different solubilities on two clay soils in southern Brazil. The following B sources were used: boric acid (17% B), ulexite (10% B), and disodium octaborate (21% B). Two experiments were conducted, one in soil columns and the other in the field. B leaching along soil columns under simulated edaphoclimatic conditions was not influenced by B source at the tested rate (1.1 kg ha−1 B). The three sources were effective in raising B content in the 0.00–0.20 m layer. On average, 60% of the added B remained in the soil following percolation with distilled water. In the field experiment, plots treated with ulexite or disodium octaborate at a rate of 1 kg ha−1 B had higher soybean yield than the untreated control. The results indicate that other factors besides solubility can influence the effectiveness of pre-sowing application of sources of B to improve soybean nutrition and yield.